PENGARUH PENDAPATAN PREMI DAN BEBAN KLAIM TERHADAP LABA BERSIH PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI (BURSA EFEK INDONESIA) - Jaka Maulana; Uswatun Hasanah (Universitas Logistik dan Bisnis Internasional, 2026)
In an increasingly modern era like today, the role of insurance companies is increasigly important in maintaining economic stability and providing protection against risks for both individuals business entities and the government. The sustainability of insurance company operations is highly dependen ton the balance between the company’s two main financial components: premium income and claim expense. The fluctuations in the net profit of insurance businesses listed on the IDX (Indonesian Stock Exchange) serve as the backdrop for this study. The results of this study show that partially premium income has a significant positive effect on net profit, partially claims expenses has a significant negative effect on net profit. And simultaneously, premium income and claim expense have a significant effect on net profit.